Ecohealth research in practice innovative applications of an ecosystem approach to health - Charron, Dominique F. (Ottawa International Development Research Centre New York Springer, 2012)
This book details an ecosystem approach to health in developing regions of the world. It demonstrates how ecohealth research has led to sustained improvements and presents evidence of real changes in conditions of people, their health and their ecosystems.
Exploring the linkages between ecosystems and human health -- Evolution towards an ecosystem approach to public health -- Ecosystem approaches to human health: key concepts and principles -- Community-based participatory research for ecohealth -- The process of conducting an ecohealth research project: a participatory action research approach -- Applying an ecosystem approach to community health research in Ghana: a case study -- Planning for a healthy community: a case study: phase II -- Challenges and ethical dilemmas in conducting participatory ecohealth research -- Ecosystem approaches to indigenous health -- Policy frameworks on health and environmental linkages -- Applying critical theory to environmental and health issues -- Examining environmental problems from a critical perspective -- Examining public health concerns from a critical perspective -- Towards a critical approach to ecohealth research and practice.
Keywords: Environmental health -- Research; Medicine